Scientific substantiation of approaches to physical rehabilitation of children with recurrent bronchial obstruction - I.A. Karimdzhanov; U.I. Zakirova; N.A. Israilova; N.B. Sodikova (Zaslavsky O.Yu., 2023)
Background. The main objectives of the treatment of bronchopulmonary diseases in children are to control the disease, achieve a stable remission of the process, restore the function of external respiration, the nervous system, increase the body's tolerance to the action of allergens. Kinesiotherapy is one of the most effective methods in non-drug rehabilitation. The purpose of our study was the pathogenetic justification of the use of kinesiohydrotherapy by the method of controlling the function of external respiration at the stage of rehabilitation of children with recurrent bronchial obstruction. Results. A comparative analysis of spirometric indicators in children with recurrent bronchial obstruction before and after kinesiohydrotherapy in the experimental and control groups showed the effectiveness of the method of comprehensive rehabilitation with the inclusion of kinesiohydrotherapy with special breathing exercises on land and in the pool. After a one-year rehabilitation period, violations of the ventilation capacity of the lungs by the obstructive type maintained in mild form. Сhildren with recurrent bronchial obstruction who did not effectively use physical rehabilitation with additional medical recommendations and physiotherapy as in experimental group, still had violations of the function of external respiration during the recovery period. Clinically, the children of control group continued to have frequent relapses of bronchial obstruction on the background of acute respiratory infections. Therefore, they belong to the group with a prolonged course of bronchial obstruction and the risk of transition to bronchial asthma. After the course of treatment, the cough became much less frequent, there were no night attacks, and the body temperature was steadily normal. Auscultation of wheezing was not heard, breathing had a harsh tinge. Conclusions. Thus, the use of therapeutic water procedures and respiratory physical exercises, i.e. kinesiohydrotherapy, is an effective method in the rehabilitation of children with recurrent bronchial obstruction.